2010
DOI: 10.1590/s0103-50532010001200017
|View full text |Cite
|
Sign up to set email alerts
|

Significant anti-inflammatory properties of a copper(II) fenoprofenate complex compared with its parent drug: Physical and chemical characterization of the complex

Abstract: A síntese, a caracterização físico-química, as propriedades anti-inflamatórias e a atividade mimética de catecolase do complexo de cobre(II) com a droga anti-inflamatória non-esteroidal Fenoprofeno [ácido 2-(3-fenóxifenil)propiônico] com fórmula [Cu 2 (fen) 2 (dmf) 2 ] (fen = ânion do fenoprofenato, dmf = N,N-dimetilformamida) foram investigadas. Os resultados da análise espectroscópica (espectros de FTIR e EPR) e dados de análise termogravimétrica e térmica diferencial obtidos para o complexo sólido estão de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 38 publications
4
14
0
Order By: Relevance
“…The pyridine-containing complexes exhibited the lowest affinity for CT-DNA and the lowest ability to displace EtBr from its EtBr·DNA complex. 16) were prepared. [11,91] The manganese(II) complex of niflumic acid -[Mn(nifl) 2 -(H 2 O) 4 ] (279, Scheme 35) -bound through an intercalative mode to CT-DNA.…”
Section: Concluding Remarks On the Complexes With Antiproliferative Amentioning
confidence: 99%
See 2 more Smart Citations
“…The pyridine-containing complexes exhibited the lowest affinity for CT-DNA and the lowest ability to displace EtBr from its EtBr·DNA complex. 16) were prepared. [11,91] The manganese(II) complex of niflumic acid -[Mn(nifl) 2 -(H 2 O) 4 ] (279, Scheme 35) -bound through an intercalative mode to CT-DNA.…”
Section: Concluding Remarks On the Complexes With Antiproliferative Amentioning
confidence: 99%
“…The selective inhibition index with COX-2 [IC 50 (COX-1)/IC 50 (COX-2)] of 9 was 3.3, whereas that of asp was 0.4. [11,16] The copper(II) ternary complexes of fenoprofen and either imidazole (im) or caffeine (caf ) -of formulae Cu(fen) 2 (im) 2 (11) and Cu 2 (fen) 4 (caf ) 2 (12) -enhanced and prolonged anti-inflammatory properties in mice relative to those of the parent drug calcium fenoprofenate. [11,15] The complex of fenoprofen (fen) of formula [Cu 2 (fen) 4 (DMF) 2 ] (10, Scheme 12) was tested in vivo for anti-inflammatory properties in comparison with fenoprofen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequency of ν as and ν s (C=O) vibration depends on the coordination of the metal ion with carboxyl group from ligands. On the basis of the FTIR spectra in ν(CO) vibration area information about ligand identicity can be obtained (monodentate, bidentate, bridge-ligand), mode of coordination to the metal ion, the type of donor atoms, as well as the type of the complex (mononuclear, binuclear and polynuclear) [29][30][31][32][33]. On the basis of these data the difference in frequency of 175 cm -1 between ν as and ν s (C=O) vibration in FTIR spectra of Cu-CMD shows that CMD carboxyl group is acting like a bidentate ligand and it is understandable that, due to electron delocalization, order of bonds is changing from ligand to the complex compound.…”
Section: Synthesis Of Complexesmentioning
confidence: 99%
“…Ternary copper(II) complexes of Fenoprofen are promising therapeutic agents against inflammatory diseases because of their enhanced anti-inflammatory and analgesic effects compared to the parent Fenoprofen calcium salt [ 16 , 17 ]. It was also demonstrated that two copper(II) complexes of Fenoprofen do not produce toxicological effects in mice after a subacute exposure, making this finding interesting for the potential employment of the formulations in possible clinical treatment.…”
Section: Introductionmentioning
confidence: 99%